STRATEGI PENGEMBANGAN PONDOK PESANTREN DALAM ERA GLOBALISASI DI KABUPATEN BANYUWANGI - Abdul Kholiq Syafa'at; Siti Aimah; Lely Ana Ferawati Ekaningsih; Mahbub Mahbub (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
This study was conducted to identify and analyze the external factors that can lead to opportunities and threats, as well as internal factors are the strengths and weaknesses for boarding, so we can know what strategies are suitable to appliedi schools in an effort to increase its presence as an Islamic educational institutions in the environment conditions that have changed into modern one. The focus of research is the development strategy of boarding school in an effort to maintain its existence as educational institutions in the era of globalization. This type of research is qualitative research. Data analysis methods used are: a qualitative analysis, which is a series of activities to analyze the data in the study objects that are not expressed in the figures using SWOT analysis. Research results indicate that the development of appropriate strategies to be implemented in the pesantren of Banyuwangi regency there are :1) development of Islamic educational institutions there are two, namely:consistent and adaptive, 2) renewal of pesantren management by application of professional management, 3) improving resource there are namely: enhancement of human resources and improvement of Natural Resources.